Translation and Validation of Indonesian Version of Scleroderma Health Assessment Questionnaire - Irma Ruslina Defi; Jennie Jennie; Vitriana Vitriana; Farida Arisanti (Faculty of Medicine, Universitas Padjadjaran, 2020)
Systemic sclerosis (SSc) or Scleroderma is a chronic autoimmune disease characterized by vasculopathy, fibrosis, and autoimmunity. Scleroderma Health Assessment Questionnare (SHAQ) is a measurement of SSc that is more specific than Health Assessment Questionnaire (HAQ) disability index(DI) to measure disability and function.The aim of this study was to translate SHAQ into Indonesian language and assess its validity and reability. The SHAQ was translated into Indonesian language and then back translated to ensure the meaning. The Indonesian version was then applied to the SSc outpatients. The validity of HAQ-DI and VAS scores was assessed using Pearson Product Moment Correlation and Cronbach’s alpha for the reability test of SSc HAQ score. To determine the convergent validity, comparisons were made between HAQ-DI, Scleroderma Visual Analog Scale (VAS), and Short Form 36 (SF 36). Eighteen females, ranging between 42 to 66 years old, were included in this study from Desember 2019 to February 2020. The results of the validity test in all variables of HAQ-DI and SSc-VAS were valid (r-count >0.361). Cronbach’s alpha for these variables were higher than the standardized items (r > 0.700), reflecting very good reability and acceptable. There was a statistically significant correlation between SSc HAQ score and HAQ-DI with most of SF-36 physical domains, except for general health.The Indonesian version of SHAQ demonstrates a good construct and discriminant validity as well as the reproducibility. Thus, it can be used for measuring disability in systemic sclerosis patients. Translasi dan Validasi Scleroderma Health Assessment Questionnaire versi Bahasa IndonesiaSklerosis sistemik atau skleroderma merupakan penyakit autoimun kronik dengan vaskulopati, fibrosis dan autoimunitas. Scleroderma Health Assessment Questionnaire (SHAQ)menilai disabilitas dan fungsi pada pasien sklerosis sistemiklebih spesifik dibandingkan Health Assessment Questionnaire (HAQ) Disability Index (DI). Tujuan dari penelitian ini adalah menerjemahkan SHAQ ke dalam bahasa Indonesia dan menilai validitas serta relialibilitasnya. Scleroderma Health Assessment Questionnaire diterjemahkan ke dalam bahasa Indonesia dan kemudian dilakukan translasi balik lalu kuesioner diisi oleh pasien sklerosis sistemik rawat jalan. Tes validitas HAQ-DI dan Visual Analog Scale (VAS) dinilai menggunakan korelasi Pearson dan reliabilitas menggunakan Cronbach’s alpha. Perbandingan antara HAQ-DI, Scleroderma-VAS, dan Short Form 36 (SF 36) dilakukan untuk menilai validitas konvergen. Subjek terdiri dari 18 orang wanita yang berusia antara 42 sampai 66 tahun dari Desember 2019 sampai Februari 2020. Hasil validitas pada semua parameter HAQ-DI dan SSc-VAS ditemukan valid (r hitung>0,361). Terdapat reliabilitas yang baik dilihat dari nilai Cronbach’s alpha yang lebih tinggi dari nilai r tabel (r>0,700). Terdapat korelasi yang signifikan antara Skleroderma-HAQ dan HAQ-DI dengan domain SF-36 kecuali domain kesehatan umum. Simpulan, bahwa SHAQ versi Indonesia memiliki konstruk dan validitas diskriminan serta reproduktifitas yang baik sehingga dapat digunakan untuk menilai disabilitas pada pasien sklerosis sistemik.